2019
DOI: 10.1002/jbm4.10206
|View full text |Cite
|
Sign up to set email alerts
|

Despite Genetic Iron Overload, Hfe‐Hemochromatosis Mice Do Not Show Bone Loss

Abstract: One of the most prevalent genetic iron overload disorders in Caucasians is caused by mutations in the HFE gene. Both HFE patients and Hfe‐mouse models develop a progressive accumulation of iron in the parenchymal cells of various tissues, eventually resulting in liver cirrhosis, hepatocellular carcinoma, cardiomyopathies, hypogonadism, and other pathologies. Clinical data and preclinical models have brought considerable attention to the correlation between iron overload and the development of osteoporosis in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“… 27 However, in various mouse models of genetic HFE -hemochromatosis, Wagner et al demonstrated that iron overload alone is not sufficient to induce bone loss. 28 Our results are consistent with this finding. The impact of cirrhosis on bone is difficult to evaluate on account of the presence of numerous cofactors for osteoporosis, such as hypogonadism and excessive alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
“… 27 However, in various mouse models of genetic HFE -hemochromatosis, Wagner et al demonstrated that iron overload alone is not sufficient to induce bone loss. 28 Our results are consistent with this finding. The impact of cirrhosis on bone is difficult to evaluate on account of the presence of numerous cofactors for osteoporosis, such as hypogonadism and excessive alcohol consumption.…”
Section: Discussionsupporting
confidence: 92%
“…Preclinical studies in Hfe −/− mice have also reported significant bone resorption induced by iron overload in long bones, 19,20 although contradictory results also exist. 21 Our data show that iron deposition found in the periodontium of Hfe −/− mice was associated with bone resorption as demonstrated by an increased CEJ-ABC distance. In addition, RT-qPCR and IHC further revealed that Hfe −/− mice led to decreased expression of the bone markers Opn and Ocn, which are associated with periodontal tissue homeostasis, wound healing and regeneration.…”
Section: Discussionsupporting
confidence: 49%
“…19,20 However, a more recent study showed that these animals have no microarchitecture impairment of long bones in a gender-and age-dependent manner. 21 Nevertheless, these animals represent an ideal model with which to investigate the correlation between periodontitis and HH. Using this approach, the aim of this study was to determine the relative amounts of iron loading in the periodontium and periodontal bone loss, as well as bone and inflammatory marker expression in Hfe −/− mice compared to control wild-type (WT) mice.…”
mentioning
confidence: 99%
“…It has also been observed that other subtypes of HH can be caused by mutations in the hepcidin antimicrobial peptide (HAMP) gene-encoding hepcidin or the main inducer genes (such as HFE, transferrin receptor-2 gene (TfR2), and hemojuvelin gene (HJV)) associated with hepcidin expression (Camaschella et al, 2000;Roetto et al, 2003;Papanikolaou et al, 2004). HFE gene mutations are primarily characterized by systemic iron overload in multiple tissues, such as the tissues in the liver, heart, and kidney (Wagner et al, 2019). It has been recently reported that the iron content increased consistently in patients suffering from HH (Kent et al, 2015), However, the researchers did not explore the relationship between iron levels and the severity of the arthritic disease.…”
Section: Osteoarthritic Joint Complications In Hereditary Hemochromat...mentioning
confidence: 99%